2010
DOI: 10.1007/s10532-010-9397-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hexose and pentose in pre-cultivation of Candida guilliermondii on the key enzymes for xylitol production in sugarcane hemicellulosic hydrolysate

Abstract: The evaluation of hexose and pentose in pre-cultivation of Candida guilliermondii FTI 20037 yeast on xylose reductase (XR) and xylitol dehydrogenase (XDH) enzymes activities was performed during fermentation in sugarcane bagasse hemicellulosic hydrolysate. The xylitol production was evaluated by using cells previously growth in 30.0 gl(-1) xylose, 30.0 gl(-1) glucose and in both sugars mixture (30.0 gl(-1) xylose and 2.0 gl(-1) glucose). The vacuum evaporated hydrolysate (80 gl(-1)) was detoxificated by ion ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
3
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 41 publications
4
18
3
10
Order By: Relevance
“…This behaviour can be explained by differences in the composition of each culture medium. In addition to D-xylose, sugarcane bagasse hydrolysates contain other sugars such as glucose and arabinose, as well as inorganic compounds such as manganese, iron, magnesium, nickel, calcium, sodium, potassium and chromium, and vitamins and amino acids (Arruda et al 2011). All of these compounds could serve as macro and micronutrients for yeast growth by increasing the xylitol production.…”
Section: Xylitol Production In D-xylose Supplemented Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…This behaviour can be explained by differences in the composition of each culture medium. In addition to D-xylose, sugarcane bagasse hydrolysates contain other sugars such as glucose and arabinose, as well as inorganic compounds such as manganese, iron, magnesium, nickel, calcium, sodium, potassium and chromium, and vitamins and amino acids (Arruda et al 2011). All of these compounds could serve as macro and micronutrients for yeast growth by increasing the xylitol production.…”
Section: Xylitol Production In D-xylose Supplemented Mediummentioning
confidence: 99%
“…For the production of xylitol via biotechnology, hemicellulose hydrolysates obtained from lignocellulose materials can be used as substrates (Arruda et al 2011;Mohamad et al 2015). Lignocellulose materials are composed of the carbohydrate polymers cellulose (35-50 %) and hemicellulose (20-35 %) and an amorphous tridimensional macromolecule, lignin (10-25 %) (Saha 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Xylose, along with glucose, is a major sugar derived from the hydrolysis of lignocellulosic biomass, among other sugars such as mannose, galactose, arabinose and rhamnose (all of them with countless applications in both pharmaceutical and food industries) [10]. d-xylose is the second most abundant sugar in nature, and a process that can be performed to convert xylose to xylitol, a polyol with wide applicability in the food and pharmaceutical industries [11], plays a significant economic role regarding biomass employment [12].…”
Section: Introductionmentioning
confidence: 99%
“…Arruda et al (2011) performed a fermentation in Erlenmeyer flasks (125 ml) containing 50 ml of the medium (pH 5.5), on a rotary shaker at 200 rpm, 30°C for 120 h and used C. guilliermondii yeast in sugarcane bagasse hemicellulosic hydrolysate with 70 g L -1 xylose. They reported that the xylitol production and Yp/s were 40 g L -1 and 0.6 g g -1 , respectively.…”
Section: Xylitol Productionmentioning
confidence: 99%